Trophic State of The Bandar Kayangan Lembah Sari Reservoir, Rumbai Pesisir Sub-District, Pekanbaru Based on TSI (Trophic State Index) - Friska Junita Sirait; Madju Siagian; Tengku Dahril Siagian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Trophic State Index can be used to determine the trophic state of waters. The TSI was calculated based on physical, chemical and biological parameters and it is more representative for analyzing the trophical state of waters. To understand the trophic state of the Bandar Kayangan Lembah Sari Reservoir, a research has been conducted in March - April 2018. There were four sampling stations, namely station 1 (in the inlet, from the Ambang River), station 2 (in the inlet from the Merbau River), station 3 (in the middle of the lake) and station 4 (in the dam). In each station there were three sampling points, in the surface, in the middle of water column, and in the base of the river. Sampling were conducted 3 times, once/week. Water quality parameter measured were chlorophyll-a, total phosphorus, transparency, temperature, pH, dissolved oxygen, and free carbondioxide. Trophic status was calculated based on Carlson’s Trophic State Index (TSI). The water quality parameter values were as follows: transparency 65.17-74.33 cm, total phosphorus 0.20-0.54 mg/L, chlorophyll-a 13.76-19.56 μg/L, depth 148.67-485 cm, temperature 27.33-29.33oC, pH 5, dissolved oxygen 4.10-7.69 mg/L, and free carbondioxide 3.32-7.32 mg/L. Trophic State Index value of the Bandar Kayangan Lembah Sari Reservoir was 68.17-72.25, and it indicates that the Bandar Kayangan water is inmedium to heavy eutrophic condition. Keywords:Ambang River, Merbau River, Carlson’sTrophic State Index, Water Quality